Kulturowo-edukacyjny wymiar rewitalizacji miasta = Cultural and educational aspect of urban regeneration - Leszkowicz-Baczyński, Jerzy (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The paper proposes the implementation of a cultural revitalization programme related to Zielona Góra?s wine monuments and artefacts. It is based, on the one hand, on an analysis of materials concerning the local cultural resources of the city and, on the other, on modern urban policies, cultural revitalisation and cultural quarters. The desk research analysis was supported by the techniques of participatory observation and a research walk. The proposed regeneration project can be considered innovative, due to the combination of the idea of social revitalisation with the cultural quarters project, which has not yet been used in Poland. The last part of the text considers the assumptions related to the educational project, which can be created on the basis of the adopted solutions, and defines the principles of educational activities not yet applied to the subject of wine.
Keywords: rewitalizacja kulturowa; dziedzictwo winiarskie; polityka miejska; edukacja; zabytki; urban regeneration; cultural revitalisation; wine heritage; urban policy; monument; education